Periostin regulation and cartilage degradation early after anterior cruciate ligament reconstruction - Jacobs, Cale A.; Keller, Laura E.; Zhang, Sheng; Fu, Qin; Hunt, Emily R.; Stone, Austin V.; Conley, Caitlin E. W.; Lattermann, Christian; Fortier, Lisa A. (Inflammation research, 2023)
Objective and design The purpose of this study was to explore pathological processes during the first 4 weeks after anterior cruciate ligament reconstruction (ACLR). Subjects Sixteen ACL-injured patients (8 females/8 males, mean age = 19.1, mean BMI = 28.6). Methods Arthrocentesis was performed 1 and 4 weeks after ACLR. Proteins in the synovial fluid were identified using nanoLC–ESI-MS/MS. Differentially up- or down-regulated proteins were identified and quantified, and a pathway analysis was performed. All identified proteins were mapped into a protein–protein interaction (PPI) network, and networks of PPIs with a combined score > 0.9 were then visualized. Results Seven pathways were upregulated after ACLR: PI3K-AKT signaling pathway, extracellular matrix (ECM)–receptor interaction, focal adhesion, protein digestion and absorption, ameobiasis, and platelet activation. Network analyses identified 8 proteins that were differentially upregulated with strong PPI interactions (periostin and 7 collagen-related proteins). Increases in periostin moderately correlated with increases in a synovial fluid biomarker of type II cartilage degradation ( ρ = 0.51, p = 0.06). Conclusion Pro-inflammatory pathways and periostin were upregulated after ACLR. Periostin demonstrated strong network connections with markers of collagen breakdown, and future work is needed to determine whether periostin may offer a biomarker of early cartilage degradation after ACLR and/or play an active role in early post-traumatic osteoarthritis (PTOA) progression.